The Effects of Jigsaw technique on high school EFL students' paragraph writing : - Nguyễn, Thị Thu Hiền (Trường Đại học Cần Thơ, 2020)
This current study aimed to investigate whether there was any positive effect of Jigsaw technique, a type of cooperative learning, on students’ writing ability in writing paragraphs and explore students’ attitude to the use of Jigsaw technique in teaching writing paragraphs. Both quantitative and qualitative methods were enhanced to collect data in the forms of a quasi-experimental design. Two involved classes including 71 tenth graders (n=71) at a senior high school in Mekong Delta were randomly assigned as the experimental group and the control group. While writing tests are administered to measure paragraph writing performance of the participants before and after the intervention, questionnaires and interviews are executed to obtain quantitative data of their attitudes towards the Jigsaw technique. The result of data analysis indicated that most of the participants has positive attitude towards the use of Jigsaw technique in teaching paragraph writing. Remarkably, the Jigsaw technique enhance three aspects of students’ writing namely organization, content and vocabulary although it had no effects on the overall quality of students’ paragraph writing.